Influência de óxidos metálicos e pequenas moléculas na performance e estabilidade de células solares orgânicas - Gavim, Anderson Emanuel Ximim (2022)
Organic solar cells (OSCs) have been produced with organic semiconductors thin films with interesting properties such as low weight and thickness, flexibility, high transparency, easy processability and abundance of materials, when compared with other commercial technologies. However, these devices still require efforts to increase the operation stability in the ambient atmosphere. This thesis focused on materials and processes aiming to increase the stability in air. These procedures were applied at the active layer and intermediary layer, as follows. OSCs were built using perylene diimide derivatives as electron acceptors, specifically N,N′-Bis(3-pentyl)perylene-3,4,9,10-bis(dicarboximide) (PDIC5), a promising material due to its high thermal and chemical stability and low cost. The optimized ITO/PEDOT:PSS/PTB7-Th:PDIC5(CN 0.5 %)/Ca/Al device presented η of 2 %. Therefore, in order to understand the effect of the CN additive in the active layer, these films were probed by AFM, UV-Vis absorbance and changes in optical properties were analyzed using the transfer matrix method (TMM). AFM images pointed out that the PTB7-Th:PDIC5 film surface is composed of nanostructures with length of 500 nm and diameter of 100 nm, resulting in Rrms of 13 nm. Moreover, significant changes in morphology were observed in PTB7-Th:PDIC5(CN 0.5 %), this film surface is more homogeneous, without visible microsized aggregates and presented lower Rrms value of 7 nm. UV-VIS spectra acquired from PTB7-Th:PDIC5(CN 0.5 %) film pointed out increased absorbance when compared with the as cast film (without CN). This result may be related with a reduced reflectance/light scattering arising from reduced surface roughness. Moreover, since the absorbance spectra presented changes in the absorbance bands, inclusive with changes in the film color (from light bordeaux to blue), changes in optical properties were evaluated with theoretical method denoted as transfer matrix method (TMM), this allows to obtain the absorption profile and optical electric field intensity along the device. Moreover, this model takes in count the experimental values of refractive index n and extinction coefficient k to simulate the spatial distribution of the electrical field and provide information about photovoltaic parameters, for instance the maximum current density (Jsc_max) that can be achieved. For this purpose, n and k spectra were acquired through ellipsometry spectroscopy from PTB7-Th:PDIC5 and PTB7-Th:PDIC5(CN 0.5 %) thin films. The results pointed out that varying the thickness of the PTB7-Th:PDIC5 the Jsc_max is at the order of 16-19 mA/cm2 with thickness at the order of 120-150 nm. The experimental Jsc values were 2.2 mA/cm2 to 8.2 mA/cm2 from devices having PTB7-Th:PDIC5 and PTB7-Th:PDIC5(CN 0.5 %) active layers, respectively. Therefore, compared with the theoretical limit of Jsc, this parameter can be improved by optimizations in morphology and interfaces to improve the charge transport and collection at the electrodes. Concerning the influence of the intermediary layer in the stability, this work replaced the conventional PEDOT:PSS hole transporting layer by MoO3 thin films produced by ultrasonic method from aqueous nanoparticles suspensions produced by Laser Ablasion in Liquids. This method allowed the production of thin films with controlled thickness (~ 2 nm), short deposition times (40 s) and large areas. The resulting MoO3 NPs are water suspended with an average size of 23 nm. Subsequently, to produce hole injection layers (HIL) for solar cells, these nanoparticles were processed as thin films onto indium tin oxide (ITO)/glass substrate using ultrasonic spray deposition, which allows fast and uniform deposition in large areas with controllable thickness and low roughness; the water is removed by heating the substrate during the processing. Moreover, scanning electronic microscopy images pointed out that the bottom of the films is mainly composed of small nanoparticles. Thereafter, the optimized glass/ITO/MoO3NPs/PTB7:PC71BM/Ca/Al solar cells displayed open circuit voltage (Voc) of 0.75 V, short circuit current density (Jsc) of 13 mA/cm2, fill factor (FF) of 58% and power conversion efficiency of 5.7% under AM1.5 illumination, presenting increased stability when compared with devices having polymeric hole transporting layer. Since LASiS method does not require the use of organic precursors/solvents, it is a green route to produce MoO3 NPs. In addition, the ultrasonic spray deposition is a versatile method to achieve homogeneous and transparent thin films from water suspended nanoparticles. The organic solar cell response pointed out the potential use of these procedures to produce hole injection layers for photovoltaic devices.Therefore, both subjects studied in this thesis, PDIC5 as electron acceptor and the use of MoO3 NPs as HIL, are promising approaches with benefits for the operation stability of OSCs.